Suitable Fertilizer Application Depth Enhances the Efficient Utilization of Key Resources and Improves Crop Productivity in Rainfed Farmland on the Loess Plateau, China - Chen, Guangzhou; Cai, Tie; Wang, Junying; Wang, Yuhao; Ren, Liangqi; Wu, Peng; Zhang, Peng; Jia, Zhikuan (Frontiers in Plant Science, 2022)
Appropriate fertilizer application methods can help to improve crop yields. However, limited information is available regarding how different fertilizer application depths might affect crop production in dryland winter wheat-summer maize cropping in the Loess Plateau region of China. Therefore, we conducted field experiments in 2019-2020 and 2020-2021 to evaluate the effects of changing the fertilizer placement depth on summer maize (current crop) and winter wheat (succeeding crop) productivity, as well as the resource use efficiency and soil nitrate nitrogen residue (SNR) level. Four fertilizer placement depths were tested comprising 5 cm (FD5), 15 cm (FD15), 25 cm (FD25), and 35 cm (FD35). The nitrogen uptake by summer maize in the two seasons was 10.0%, 6.5%, and 11.8% higher under FD15 compared with those under FD5, FD25, and FD35, respectively, because FD15 effectively increased the root length density, root surface area density, and rate of root bleeding sap. Due to the increased nitrogen uptake, the leaf area index, plant height, stem diameter, and accumulated dry matter were improved in summer maize. The interception of photosynthetically active radiation was 3.6%, 3.7%, and 5.9% higher under FD15 compared with those under FD5, FD25, and FD35, respectively. The summer maize grain yield increased by 13.9–22.4% under FD15 compared with the other treatments. In addition, the SNR in the deep soil (200–300 cm) was significantly lower under FD15 at the summer maize harvest (17.9–30.7%) compared with the other treatments. Moreover, FD15 increased the winter wheat (succeeding crop) grain yield (2.6–11.2%) and reduced the SNR in the 200–300 cm soil layer (8.8–16.5%) at the winter wheat harvest. The highest radiation use efficiency, precipitation use efficiency, and nitrogen use efficiency were obtained under FD15 in both summer maize and winter wheat. These results clearly suggest that a depth fertilization of 15 cm enhanced the productivity and resource use efficiency for the current and subsequent crops in rainfed farmland in the Loess Plateau of China, as well as reducing the SNR in the deep soil to promote sustainable agricultural development. These findings provide a practical reference for optimizing fertilizer application management.